Developing the business model to increase the provided value - Lindell, Ludvig; Lundgren, Jesper (My University, 2022)
This master thesis has investigated what challenges an exclusive importer of marine commercial powertrains have regarding their business model and how to overcome them. The emphasis in the study has been on how the importer should add more value in the supply chain and how it should incorporate these activities into a coherent business model. Due to the exclusivity agreement with its powertrain manufacturer, this case study has focused on the importer itself and its resellers, as that is the domain in which the importer has the freedom of acting. The study has been conducted through qualitative interviews with key management personnel at the importer as well as people in managing positions at several of the importer’s resellers. The data collected has been analyzed using relevant theoretical concepts such as resource-based view, business models, as well as theories on supply chain strategies. The analysis regards how and what value the importer should provide to its resellers to better help their businesses and to increase revenues. Lastly, the thesis concludes with a recommendation to the importer of closer collaboration and partnerships with its resellers, to mitigate the identified challenges and provide more value.
Keywords: business model; intermediary; marine powertrain importer; value; supply chain strategy